Educação financeira na educação básica: uma proposta didática a partir do letramento financeiro - ARAÚJO, Atalia de (Universidade Federal do Tocantins, 2023)
Financial Education is related to our daily lives and there are no doubts that should be taught since Basic Education, as it can help in the consumption habits of society. In view of this, this work tried to answer the following question: How to approach concepts of Financial Education in Basic Education? The main objective of this research was to develop a methodological approach aimed at teaching Financial Education. The methodology used to carry out the study was bibliographic research, together with the creation of records for the registration of data and conceptual information that were articulated in the design of a didactic proposal. As a result, we highlight the presentation of a didactic proposal that respects planning guidelines, which was organized in the form of a fair for the exploration of financial concepts in a dynamic and illustrative way from the levels of Financial Literacy and the objectives of the National Strategy for Financial Education-ENEF. The proposal was called